2017
DOI: 10.1002/marc.201700251
|View full text |Cite
|
Sign up to set email alerts
|

Benzoxazine/Triphenylamine‐Based Dendrimers Prepared through Facile One‐Pot Mannich Condensations

Abstract: A series of thermally polymerizable dendrimers of various generations, equipped with triphenylamine (TPA) and benzoxazine (BZ) groups, is synthesized through facile one-pot Mannich condensations of N ,N -bis(4-aminophenyl)benzene-1,4-diamine (TPA-3NH , as the core group), 4-(bis(4-aminophenyl)amino)phenol (TPA-2NH -OH, as the AB branching group), and CH O in 1,4-dioxane. The ratios of the integrated areas in the H nuclear magnetic resonance spectra of these dendrimers are consistent with the theoretical number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…† TPA-BZ DG1 [Scheme 1(c)] was synthesized following an approach we have described previously. 41 In our design strategy, the hyperbranched TPA-BZs were developed in the direction from the focal group or from the terminal groups of TPA-BZ monomer and TPA-BZ trimer (Scheme 2), respectively. Scheme 2A presents the two different directions for the chemical development of the TPA-BZ monomer-from its focal group to form the symmetrical TPA-BZ DG1 (downward) or from its terminal groups to form the asymmetrical TPA-BZ trimer (upward).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…† TPA-BZ DG1 [Scheme 1(c)] was synthesized following an approach we have described previously. 41 In our design strategy, the hyperbranched TPA-BZs were developed in the direction from the focal group or from the terminal groups of TPA-BZ monomer and TPA-BZ trimer (Scheme 2), respectively. Scheme 2A presents the two different directions for the chemical development of the TPA-BZ monomer-from its focal group to form the symmetrical TPA-BZ DG1 (downward) or from its terminal groups to form the asymmetrical TPA-BZ trimer (upward).…”
Section: Resultsmentioning
confidence: 99%
“…42 The UV-Vis absorption and PL emission spectra of the hyperbranched TPA-BZs featured small bathochromic shis that were affected strongly by the number of TPA groups, presumably because of the increase in the effective conjugation length. [41][42][43] Interestingly, the effective conjugation length of the TPA-BZs was not affected by the DB of the asymmetrical hyperbranched monomers, except in the case of the symmetrical dendrimers; for example, TPA-BZ DG1 possesses an effective conjugation length relatively higher than those of the asymmetrical hyperbranched TPA-BZs (e.g., TPA-BZ trimer and linear TPA-BZ tetramer) because the branching number increased signicantly for the TPA-BZ dendrimers.…”
Section: Uv-vis Absorption and Pl Emission Spectra Of Hyperbranched Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al [24] investigated the photoluminescence properties of hybrid materials based on benzoxazine-bridged polysilsesquioxanes. Lin et al [25] observed the bathochromic shifts in the UV-visible and photoluminescent spectra of thermally polymerizable triphenylamine-benzoxazine dendrimers. Li et al [26] firstly reported the benzoxazinebased polyfluorene displaying reversible temperaturesensitive fluorescent properties.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] PBZs can possess many attractive features including a high carbon residue, low surface energy, low moisture absorption, good thermal and mechanical properties, excellent dimensional stability, a stable dielectric constant, excellent flame retardancy, and good electrical properties that are not found for other traditional phenolic resins (e.g., phenolic bismaleimides, advanced epoxies). [9][10][11][12][13][14][15][16][17][18][19][20] Nevertheless, PBZs have limited applications at high temperature, because their CNC bonds break readily at temperatures above 260 °C. [21] As a result, many strategies have been tested to enhance the performance of PBZs.…”
Section: Introductionmentioning
confidence: 99%